1923-1950 Arası Dönemde Ankara Kentleşmesi ve Sorunları - İbrahim İRDEM; Asilkan LENGER (Gazi Akademik Bakış)
The period between 1923-1950 in Turkey is the years when the urbanization process progressed slowly. Until the 1950s, no urbanization movements were encountered other than the city of Ankara during the period. Ankara entered a process of rapid growth and immigration along with the declaration of it as the capital city in 1923. After becoming the capital, Ankara, by evolving into a construction site and along with the continuous immigration, witnessed the process in which the prices of houses, lands and rents increased rapidly. Although the attempts to modernize the city aimed to make Ankara an exemplary city for the young Turkey, the social, economic and cultural changes as well as physical changes in the city also led to the emergence of structural disorders and security problems arising from urbanization. In this study, the problems brought about by the urbanization process that took place in Turkey until the 1950s will be discussed over the city of Ankara. Including the urbanization of Ankara in the period between 1923-1950 in the study is very important in terms of shedding light on the historical process that affected the emergence of the urban problems Ankara is facing today. Therefore, the basic assumption of this study is creating the idea that the problems of Ankara urbanization today should be sought in the early Republic period. In the study, document analysis and secondary data were used methodologically.